Indicatives of ancient conditions of sea level stability on the southern Pernambuco continental shelf - MICHELLI, MAXIMILIANO; ARAÚJO, TEREZA; MAIDA, MAURO; VITAL, HELENICE (Pesquisas em Geociências, 2001)
The continental shelf in southern Pernambuco State (Brazilian Northeast) is characteristically narrow, and breaks around 32km from the actual coastline, in depths of 50 to 60m. The sediments on this shelf are similar in their constitution to the rest of the Brazilian Northeastern shelf, showing a prevailing fraction of coarse carbonatic sands. There is also a significant input of terrigenous material, which may be found mainly up to 20m deep. Regarding it’s geomorphology, Pernambuco’s southern shelf presents a soft slope, with long and smooth surfaces, sometimes crossed by meandering channels which show more frequently next to river mouths. Indicatives of sea level change like the presence of beach rocks and paleochannels occur along the shelf. The main interest of the present work lies on the location and characterization of the submerged beachrocks on the southern portion of Pernambuco State continental shelf. The area was investigated using sonographic techniques. Data analysis allowed to identify indicatives of ancient conditions of sea level stability on the shelf. The first evidence was found at a depth of 20m, where a beachrock of a triangular shape and rounded top with 136m wide and 6m height, was identified. The second evidence was registered at 40 to 50m depth also represented by a beachrock. Geomorphologically this second feature presents a relatively flat top, 209m of width and 4m height. Another structure indicative of sea level change identified was a paleochannel, which started at 30m depth and followed the direction northwest-southeast on the shelf.